Multiple Strains of Trichomonas gallinae are Widespread in Reservoir Hosts and Environmental Resources in UK Farmland - Rebecca C. Thomas; Jenny C. Dunn; Helen Hipperson; Antony J. Morris; Philip V. Grice; Keith C. Hamer; Simon J. Goodman (Molecular Ecology, 2026)
Understanding transmission routes of parasites and pathogens is critical for the development of control measures and mitigation of impacts on host populations. Trichomonas gallinae is a widespread parasite in columbids worldwide, and has emerged as a lethal disease in passerines, particularly finches. The postulated transmission route from columbids to passerines via spillover at shared resources has not yet been empirically tested. Here, we screen 363 birds (261 columbids and 102 non‐columbids) in the UK and France for the presence and strain identity of T. gallinae . To quantify potential environmental transmission, we also screened 51 food and water resources common in farmland, at 12 sites over a 2‐year period. We isolated T. gallinae parasites from 79% of columbids, 36% of non‐columbids, and 39% of environmental resources. Prevalence of the Type A strain was more than double in birds sampled at fed sites compared to those at unfed sites. Strain composition was mirrored in columbids, passerines, and shared food and water resources, providing compelling evidence that T. gallinae , especially the Type A strain, is transmitted via these shared resources. T. gallinae was isolated from high density feeding resources (where supplementary food was provided) nearly three times as often as low density resources (natural areas of seed‐providing vegetation), meaning that careful management of supplementary resources has the potential to reduce T. gallinae prevalence in wild bird populations. Further work needs to test practical means of achieving this, but ensuring any supplementary feeding is provided at low density is likely to be critical to reducing parasite transmission.

Functional composition of subsoil microbial communities changes with oak mortality - Anna C. Goodman; Ernest N. Walker; Glade D. Bogar; Laura M. Bogar (Soil Biology and Biochemistry, 2026)

First description of the male and redescription of the female of Ixodes lunatus Neumann, 1907 (Acari: Ixodidae), parasite of tenrecs and rodents in Madagascar - Dmitry A. Apanaskevich; Mariah C. Finley; Steven M. Goodman (Systematic Parasitology, 2026)

Analyzing multidrug resistance patterns across the food supply chain using association rule mining - Joshua C. Glass; Gayatri Anil; Jordan D. Zehr; Kristina M. Ceres; Laura B. Goodman; Casey L. Cazer (Preventive Veterinary Medicine, 2026)

Variation in estimates of the footprint of large, ground-mounted photovoltaic solar energy in the United States and its associated land-cover change across three datasets - Michael O. Levin; Emma Forester; Elizabeth L. Kalies; Lauren Goodman; Jason S. Hagani; Chevon C. Holmes; Noah Z. Krasner; Caitlin Markus; Jared B. Meek; Anubhav Vanamamalai; Shivani Agarwal; Uzma Ashraf; et al. (Journal of Environmental Management, 2025)

Blunted cold pressor test-induced cortisol but not total ghrelin response in women with bulimia nervosa following a standardized sweet-fat liquid meal - Kimberly R. Smith; Colleen C. Schreyer; Nicholas T. Bello; Ethan Goodman; Kellie L.K. Tamashiro; Timothy H. Moran; Angela S. Guarda (Appetite, 2025)

P01-02 Non-Sugar Sweeteners and Cancer – Integrating Results of a Systematic Review of Epidemiology Studies with Toxicology Evidence - D. Boon; S.A. Marchitti; K.J. Colonna; I.M. Chowdhury-Paulino; W. Li; A. Berky; C. Restrepo; M. Jack; J.E. Goodman (Toxicology Letters, 2025)

Gopher Tortoise (Gopherus polyphemus) burrow associate communities are depauperate in modified landscapes - George C. Brooks; Steven J. Goodman; William M. Moore; Houston C. Chandler; Nicholas M. Caruso; Jennifer A. Smith; Thomas A. Gorman; Carola A. Haas (Community Ecology, 2025)
The Gopher Tortoise ( Gopherus polyphemus ) is considered a keystone species because its burrows provide refuge for an entire suite of other species (hereafter burrow associates) that occupy the habitats in which it resides. The Gopher Tortoise has declined across its range in large part due to habitat loss and land use change resulting in burrow abandonment or reduced burrow density, and the concomitant negative effects on burrow associate diversity have been well documented. However, under scenarios where Gopher Tortoise populations persist in modified habitat, the effect on community associates has received considerably less attention. In such instances, vegetation changes drive the loss of associate species, not the lack of suitable burrows. Here, we evaluated associations between Gopher Tortoise burrows and vertebrate burrow associates within test ranges and forested sites on Eglin Air Force Base, Florida. Specifically, we (1) determined how vegetation composition varies between forested sandhills and military test ranges, and (2) compared species richness, diversity, and community composition of burrow associates between habitats. We found that vegetation composition surrounding Gopher Tortoise burrows is highly variable, but in general test ranges had a simpler habitat structure and less diverse native plant communities than forested sites. As a result, we show that although military test range sites contain Gopher Tortoise burrows at comparable or higher densities than sites in natural longleaf pine sandhills, the community of vertebrate burrow associates in test range sites appears to be depauperate. Our results highlight that concern over habitat modifications may be warranted even in instances where Gopher Tortoise populations appear to be persisting. In the context of management that seeks to be beneficial to a wide array of burrow associates, efforts aimed at bolstering Gopher Tortoise populations in forested sandhills would be most prudent.

Effects of calcareous marine algae on performance, rumen fermentation and methane emissions of high-yielding dairy cows - Philip C. Garnsworthy; Neil Saunders; Jennifer R. Goodman; Shane O’Connell (Animal Feed Science and Technology, 2025)

Climate Covariate Choice and Uncertainty in Projecting Species Range Shifts: A Case Study in the Eastern Bering Sea - Maurice C. Goodman; Jonathan C. P. Reum; Cheryl L. Barnes; Andre E. Punt; James N. Ianelli; Elizabeth A. McHuron; Giulio A. De Leo; Kirstin K. Holsman (Fish and Fisheries, 2025)
Species distribution models (SDMs) are critical to the adaptive management of fisheries under climate change. While many approaches projecting marine species range shifts have incorporated the effects of temperature on movement, there is a need to incorporate a wider suite of ecologically relevant predictors as temperature‐based SDMs can considerably under‐ or over‐estimate the rate of species responses to climate shocks. As a subarctic ecosystem at the sea ice margin, the Eastern Bering Sea (EBS) is warming faster than much of the global ocean, resulting in the rapid redistribution of key fishery and subsistence resources. To support long‐term planning and adaptation, we combine 40 years of scientific surveys with a high‐resolution oceanographic model to examine the effects of bottom temperature, oxygen, pH and a regional climate index (the extent of the EBS ‘cold pool’) on range projections through the end of the century. We use multimodel inference to partition uncertainty among earth systems models, climate scenarios and distribution model parameterizations for several ecologically and economically important EBS groundfish and crabs. Covariate choice is the primary source of uncertainty for most species, with models that account for spatial responses to the cold pool performing better and suggesting more extensive northward movements than alternative models. Models suggest declines in the probability of occurrence at low pH and oxygen concentrations for most species. We project shifts that are directionally consistent with, yet larger than those previously estimated for most species, suggesting that accounting for large‐scale climate variability in species distribution models may substantially alter range projections.

Determining a representative elementary area for soil desiccation cracking - C. Clay Goodman; Farshid Vahedifard (Engineering Geology, 2025)

Marine Protected Areas That Preserve Trophic Cascades Promote Resilience of Kelp Forests to Marine Heatwaves - Joy A. Kumagai; Maurice C. Goodman; Juan Carlos Villaseñor‐Derbez; David S. Schoeman; Kyle C. Cavanuagh; Tom W. Bell; Fiorenza Micheli; Giulio De Leo; Nur Arafeh‐Dalmau (Global Change Biology, 2024)
Under accelerating threats from climate‐change impacts, marine protected areas (MPAs) have been proposed as climate‐adaptation tools to enhance the resilience of marine ecosystems. Yet, debate persists as to whether and how MPAs may promote resilience to climate shocks. Here, we use 38 years of satellite‐derived kelp cover to empirically test whether a network of 58 temperate coastal MPAs in Central and Southern California enhances the resistance of kelp forest ecosystems to, and their recovery from, the unprecedented 2014–2016 marine heatwave regime that occurred in the region. We also leverage a 22‐year time series of subtidal community surveys to mechanistically understand whether trophic cascades explain emergent patterns in kelp forest resilience within MPAs. We find that fully protected MPAs significantly enhance kelp forests' resistance to and recovery from marine heatwaves in Southern California, but not in Central California. Differences in regional responses to the heatwaves are partly explained by three‐level trophic interactions comprising kelp, urchins, and predators of urchins. Urchin densities in Southern California MPAs are lower within fully protected MPAs during and after the heatwave, while the abundances of their main predators—lobster and sheephead—are higher. In Central California, a region without lobster or sheephead, there is no significant difference in urchin or kelp densities within MPAs as the current urchin predator, the sea otter, is protected statewide. Our analyses show that fully protected MPAs can be effective climate‐adaptation tools, but their ability to enhance resilience to extreme climate events depends upon region‐specific environmental and trophic interactions. As nations progress to protect 30% of the oceans by 2030, scientists and managers should consider whether protection will increase resilience to climate‐change impacts given their local ecological contexts, and what additional measures may be needed.

An integrated agroforestry-bioenergy system for enhanced energy and food security in rural sub-Saharan Africa - Natxo García-López; Aida Bargués-Tobella; Rosa C. Goodman; Solange Uwingabire; Cecilia Sundberg; Christoffer Boman; Gert Nyberg (Ambio, 2024)
Most people in rural sub-Saharan Africa lack access to electricity and rely on traditional, inefficient, and polluting cooking solutions that have adverse impacts on both human health and the environment. Here, we propose a novel integrated agroforestry-bioenergy system that combines sustainable biomass production in sequential agroforestry systems with biomass-based cleaner cooking solutions and rural electricity production in small-scale combined heat and power plants and estimate the biophysical system outcomes. Despite conservative assumptions, we demonstrate that on-farm biomass production can cover the household’s fuelwood demand for cooking and still generate a surplus of woody biomass for electricity production via gasification. Agroforestry and biochar soil amendments should increase agricultural productivity and food security. In addition to enhanced energy security, the proposed system should also contribute to improving cooking conditions and health, enhancing soil fertility and food security, climate change mitigation, gender equality, and rural poverty reduction.

Evaluation of a novel palm-free fat supplement to reduce the carbon footprint of diets for dairy cows - Philip C. Garnsworthy; Neil Saunders; Jennifer R. Goodman (Animal Feed Science and Technology, 2024)

Exploring the nutritional value of corn fermented protein as a replacement for soybean meal in diets for juvenile channel catfish (Ictalurus punctatus): Impacts on production performance, intestinal health, and disease resistance - Fernando Y. Yamamoto; Jing Huang; C. Camilo Suarez-Barazeta; Steven R. Craig; Caitlin E. Older; Bradley M. Richardson; Thiago M. Santana; Matt J. Griffin; J. Grant Reifers; Penelope M. Goodman; Delbert M. Gatlin III (Aquaculture, 2024)

Influence of probiotic and prebiotic supplementation on intestinal microbiota and resistance to Edwardsiella ictaluri infection in channel catfish ( Ictalurus punctatus ) following florfenicol administration - Caitlin E. Older; Matt J. Griffin; Bradley M. Richardson; Geoffrey C. Waldbieser; J. Grant Reifers; Penelope M. Goodman; Cynthia Ware; Delbert M. Gatlin; David J. Wise; Fernando Y. Yamamoto (Journal of Fish Diseases, 2024)
Enteric septicemia of catfish (ESC), caused by the gram‐negative enteric bacteria Edwardsiella ictaluri , is a significant threat to catfish aquaculture in the southeastern United States. Antibiotic intervention can reduce mortality; however, antibiotic use results in an imbalance, or dysbiosis, of the gut microbiota, which may increase susceptibility of otherwise healthy fish to enteric infections. Herein, recovery of the intestinal microbiota and survivability of channel catfish in response to ESC challenge was evaluated following a 10‐day course of florfenicol and subsequent probiotic or prebiotic supplementation. Following completion of florfenicol therapy, fish were transitioned to a basal diet or diets supplemented with a probiotic or prebiotic for the remainder of the study. Digesta was collected on Days 0, 4, 8 and 12, beginning on the first day after cessation of antibiotic treatment, and gut microbiota was characterized by Illumina sequencing of the 16S rRNA gene (V4 region). Remaining fish were challenged with E. ictaluri and monitored for 32 days post‐challenge. Florfenicol administration resulted in dysbiosis characterized by inflated microbial diversity, which began to recover in terms of diversity and composition 4 days after cessation of florfenicol administration. Fish fed the probiotic diet had higher survival in response to ESC challenge than the prebiotic ( p = .019) and negative control ( p = .029) groups.

Wastewater based surveillance can be used to reduce clinical testing intensity on a university campus - Ayaaz Amirali; Kristina M. Babler; Mark E. Sharkey; Cynthia C. Beaver; Melinda M. Boone; Samuel Comerford; Daniel Cooper; Benjamin B. Currall; Kenneth W. Goodman; George S. Grills; Erin Kobetz; Naresh Kumar; et al. (Science of The Total Environment, 2024)

Europa’s coupled ice–ocean system: Temporal evolution of a pure ice shell - Nicole C. Shibley; Jeremy Goodman (Icarus, 2024)

Calcitized evaporites in the Mesoproterozoic Atar and El Meriti Groups, Mauritania, Africa - Ashley R. Manning-Berg; Emily E. Goodman; Linda C. Kah (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

A Landscape-Scale Comparison of Wetlands Associated with Surface Coal Extraction and Naturally-Occurring Wetlands in the Central Appalachian Mountains, USA - David C. Goodman; Walter H. Smith (Wetlands, 2023)

Description of a new species of Ixodes Latreille, 1795 (Acari: Ixodidae), parasite of shrew tenrecs (Afrotheria: Tenrecidae) and rodents (Rodentia: Muridae) on Madagascar - Mackenzie C. Englert; Steven M. Goodman; Dmitry A. Apanaskevich (Systematic Parasitology, 2023)

Ultraconserved elements resolve phylogenetic relationships and biogeographic history of African-Malagasy bent-winged bats (Miniopterus) - Terrence C. Demos; Paul W. Webala; Steven M. Goodman; Julian C. Kerbis Peterhans; Holly L. Lutz; Bernard R. Agwanda; Natalia Cortés-Delgado; Stefania Briones; Richard H. Ree; Bruce D. Patterson (Molecular Phylogenetics and Evolution, 2023)

Optimized conditions for the long-term growth of primary cell cultures derived from the Asian citrus psyllid, Diaphorina citri (Liviidae: Hemiptera) - Ke Wu; Grace J. Ortgiesen; Cynthia L. Goodman; Bryony C. Bonning (In Vitro Cellular & Developmental Biology - Animal, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Successful storage of Trichomonas gallinae on Whatman FTA cards following culture - Rebecca C. Thomas; Jenny C. Dunn; Chris J. Orsman; Antony J. Morris; Helen Hipperson; Philip V. Grice; Keith C. Hamer; Simon J. Goodman (Conservation Genetics Resources, 2022)
Logistical constraints concerning parasite sample storage can hinder progress with the discovery of genetic variation on a global scale. New storage methods are being developed to address this, but require testing in order to understand how widely applicable these methods are. Whatman FTA cards have been tested previously under laboratory conditions for storing low-concentration Trichomonas gallinae isolates with the conclusion that they are not suitable, but have not been tested under field conditions. Here, we conducted a field-test, comparing FTA cards with storage in ethanol for T. gallinae samples collected and cultured from wild Columbiformes in Africa using standard field methods, before transportation to the UK. After 6 months storage, both methods resulted in an overall prevalence of 100% following PCR amplification (n = 59), suggesting that FTA cards are suitable for estimation of T. gallinae prevalence. However, samples stored in ethanol produced more, and longer, sequences than those stored on FTA cards. These data suggest storage in ethanol is preferable for the acquisition of high quality genetic strain data, but that FTA cards can be used successfully to ascertain infection prevalence and identify parasite strains under field conditions.

Assessing rates of parasite coinfection and spatiotemporal strain variation via metabarcoding: Insights for the conservation of European turtle doves Streptopelia turtur - Rebecca C. Thomas; Jenny C. Dunn; Deborah A. Dawson; Helen Hipperson; Gavin J. Horsburgh; Antony J. Morris; Chris Orsman; John Mallord; Philip V. Grice; Keith C. Hamer; Cyril Eraud; Lormée Hervé; et al. (Molecular Ecology, 2022)
Understanding the frequency, spatiotemporal dynamics and impacts of parasite coinfections is fundamental to developing control measures and predicting disease impacts. The European turtle dove ( Streptopelia turtur ) is one of Europe's most threatened bird species. High prevalence of infection by the protozoan parasite Trichomonas gallinae has previously been identified, but the role of this and other coinfecting parasites in turtle dove declines remains unclear. Using a high‐throughput sequencing approach, we identified seven strains of T . gallinae , including two novel strains, from ITS1/5.8S/ITS2 ribosomal sequences in turtle doves on breeding and wintering grounds, with further intrastrain variation and four novel subtypes revealed by the iron‐hydrogenase gene. High spatiotemporal turnover was observed in T . gallinae strain composition, and infection was prevalent in all populations (89%–100%). Coinfection by multiple Trichomonas strains was rarer than expected (1% observed compared to 38.6% expected), suggesting either within‐host competition, or high mortality of coinfected individuals. In contrast, coinfection by multiple haemosporidians was common (43%), as was coinfection by haemosporidians and T . gallinae (90%), with positive associations between strains of T . gallinae and Leucocytozoon suggesting a mechanism such as parasite‐induced immune modulation. We found no evidence for negative associations between coinfections and host body condition. We suggest that longitudinal studies involving the recapture and investigation of infection status of individuals over their lifespan are crucial to understand the epidemiology of coinfections in natural populations.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Effectiveness of a Constructed Wetland with Carbon Filtration in Reducing Pesticides Associated with Agricultural Runoff - Laura B. McCalla; Bryn M. Phillips; Brian S. Anderson; Jennifer P. Voorhees; Katie Siegler; Katherine R. Faulkenberry; Maurice C. Goodman; Xin Deng; Ron S. Tjeerdema (Archives of Environmental Contamination and Toxicology, 2022)
The Salinas Valley in Monterey County, California, USA, is a highly productive agricultural region. Irrigation runoff containing pesticides at concentrations toxic to aquatic organisms poses a threat to aquatic ecosystems within local watersheds. This study monitored the effectiveness of a constructed wetland treatment system with a granulated activated carbon (GAC) filter installation at reducing pesticide concentrations and associated toxicity to Ceriodaphnia dubia , Hyalella azteca , and Chironomus dilutus . The wetland was supplied with water pumped from an impaired agricultural and urban drainage. Across five monitoring trials, the integrated system’s average pesticide concentration reduction was 52%. The wetland channel and GAC filtration components individually provided significant treatment, and within each, pesticide solubility had a significant effect on changes in pesticide concentrations. The integrated treatment system also reduced nitrate by 61%, phosphate by 73%, and turbidity by 90%. Input water was significantly toxic to C. dubia and H. azteca in the first trial. Toxicity to C. dubia persisted throughout the system, whereas toxicity to H. azteca was removed by the channel, but there was residual toxicity post-GAC. The final trial had significant input toxicity to H. azteca and C. dilutus . The channel reduced toxicity to H. azteca and removed toxicity to C. dilutus . GAC filtration reduced H. azteca toxicity to an insignificant level. There was no input toxicity in the other three trials. The results demonstrate that a wetland treatment system coupled with GAC filtration can reduce pesticide concentrations, nutrients, suspended particles, and aquatic toxicity associated with agricultural runoff.

Effects of Estuary-Wide Seagrass Loss on Fish Populations - Jennifer K. O’Leary; Maurice C. Goodman; Ryan K. Walter; Karissa Willits; Daniel J. Pondella; John Stephens (Estuaries and Coasts, 2021)

Pre-diagnosis neutrophil-to-lymphocyte ratio and mortality in individuals who develop lung cancer - Laurie Grieshober; Stefan Graw; Matt J. Barnett; Gary E. Goodman; Chu Chen; Devin C. Koestler; Carmen J. Marsit; Jennifer A. Doherty (Cancer Causes & Control, 2021)
Purpose The neutrophil-to-lymphocyte ratio (NLR) is a marker of systemic inflammation that has been reported to be associated with survival after chronic disease diagnoses, including lung cancer. We hypothesized that the inflammatory profile reflected by pre-diagnosis NLR, rather than the well-studied pre-treatment NLR at diagnosis, may be associated with increased mortality after lung cancer is diagnosed in high-risk heavy smokers. Methods We examined associations between pre-diagnosis methylation-derived NLR (mdNLR) and lung cancer-specific and all-cause mortality in 279 non-small lung cancer (NSCLC) and 81 small cell lung cancer (SCLC) cases from the β-Carotene and Retinol Efficacy Trial (CARET). Cox proportional hazards models were adjusted for age, sex, smoking status, pack years, and time between blood draw and diagnosis, and stratified by stage of disease. Models were run separately by histotype. Results Among SCLC cases, those with pre-diagnosis mdNLR in the highest quartile had 2.5-fold increased mortality compared to those in the lowest quartile. For each unit increase in pre-diagnosis mdNLR, we observed 22–23% increased mortality (SCLC-specific hazard ratio [HR] = 1.23, 95% confidence interval [CI]: 1.02, 1.48; all-cause HR = 1.22, 95% CI 1.01, 1.46). SCLC associations were strongest for current smokers at blood draw (Interaction P s = 0.03). Increasing mdNLR was not associated with mortality among NSCLC overall, nor within adenocarcinoma ( N = 148) or squamous cell carcinoma ( N = 115) case groups. Conclusion Our findings suggest that increased mdNLR, representing a systemic inflammatory profile on average 4.5 years before a SCLC diagnosis, may be associated with mortality in heavy smokers who go on to develop SCLC but not NSCLC.

Wetland Selection by Female Ring-Necked Ducks (Aythya collaris) in the Southern Atlantic Flyway - Tori D. Mezebish; Richard B. Chandler; Glenn H. Olsen; Michele Goodman; Frank C. Rohwer; Nicholas J. Meng; Mark D. McConnell (Wetlands, 2021)

Categorizing the characteristics of human carcinogens: a need for specificity - Carr J. Smith; Thomas A. Perfetti; A. Wallace Hayes; Sir Colin Berry; James E. Trosko; Judy A. King; Jay I. Goodman; C. Glenn Begley; Anthony Dayan (Archives of Toxicology, 2021)

Pantropical variability in tree crown allometry - Grace Jopaul Loubota Panzou; Adeline Fayolle; Tommaso Jucker; Oliver L. Phillips; Stephanie Bohlman; Lindsay F. Banin; Simon L. Lewis; Kofi Affum‐Baffoe; Luciana F. Alves; Cécile Antin; Eric Arets; Luzmila Arroyo; et al. (Global Ecology and Biogeography, 2021)
Aim Tree crowns determine light interception, carbon and water exchange. Thus, understanding the factors causing tree crown allometry to vary at the tree and stand level matters greatly for the development of future vegetation modelling and for the calibration of remote sensing products. Nevertheless, we know little about large‐scale variation and determinants in tropical tree crown allometry. In this study, we explored the continental variation in scaling exponents of site‐specific crown allometry and assessed their relationships with environmental and stand‐level variables in the tropics. Location Global tropics. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 87,737 trees distributed among 245 forest and savanna sites across the tropics, we fitted site‐specific allometric relationships between crown dimensions (crown depth, diameter and volume) and stem diameter using power‐law models. Stand‐level and environmental drivers of crown allometric relationships were assessed at pantropical and continental scales. Results The scaling exponents of allometric relationships between stem diameter and crown dimensions were higher in savannas than in forests. We identified that continental crown models were better than pantropical crown models and that continental differences in crown allometric relationships were driven by both stand‐level (wood density) and environmental (precipitation, cation exchange capacity and soil texture) variables for both tropical biomes. For a given diameter, forest trees from Asia and savanna trees from Australia had smaller crown dimensions than trees in Africa and America, with crown volumes for some Asian forest trees being smaller than those of trees in African forests. Main conclusions Our results provide new insight into geographical variability, with large continental differences in tropical tree crown allometry that were driven by stand‐level and environmental variables. They have implications for the assessment of ecosystem function and for the monitoring of woody biomass by remote sensing techniques in the global tropics.

Microbiota of Four Tissue Types in American Alligators (Alligator mississippiensis) Following Extended Dietary Selenomethionine Exposure - Troy J. Kieran; Samantha J. Goodman; John W. Finger; Jesse C. Thomas; Matthew T. Hamilton; Tracey D. Tuberville; Travis C. Glenn (Bulletin of Environmental Contamination and Toxicology, 2020)

Multilocus phylogeny of a cryptic radiation of Afrotropical long‐fingered bats (Chiroptera, Miniopteridae) - Terrence C. Demos; Paul W. Webala; Holly L. Lutz; Julian C. Kerbis Peterhans; Steven M. Goodman; Natalia Cortés‐Delgado; Michael Bartonjo; Bruce D. Patterson (Zoologica Scripta, 2020)
The Old World bat family Miniopteridae comprises only the genus Miniopterus , which includes 20 currently recognized species from the Afrotropical realm and 15 species from Eurasia and Australasia. Since 2003, the number of recognized Miniopterus species has grown from 19 to 35, with most newly described species endemic to Madagascar and the Comoros Archipelago. We investigated genetic variation, phylogenetic relationships and clade membership in Miniopterus focusing on Afrotropical taxa. We generated mitochondrial cytochrome‐ b (cyt‐ b ) and nuclear intron data (five genes) from 352 vouchered individuals collected at 78 georeferenced localities. Including 99 additional mitochondrial sequences from GenBank, we analysed a total of 25 recognized species. Mitochondrial genetic distances among cyt‐ b ‐supported clades averaged 9.3%, representing as many as five undescribed species. Multilocus coalescent delimitation strongly supported the genetic isolation of eight of nine tested unnamed clades. A large number of sampled clades in sub‐Saharan Africa are distributed wholly or partly in East Africa (nine of 13 clades), suggesting that Miniopterus diversity has been grossly underestimated. Although 25 of 27 cyt‐ b and 23 of 25 nuclear gene tree lineages from the Afrotropics were strongly supported as monophyletic, a majority of deep nodes were poorly resolved in phylogenetic analyses. Long terminal branches subtending short backbone internodes in the phylogenetic analyses suggest a rapid radiation model of diversification. This hypothesis needs to be tested using more phylogenetically informative data.

Viator vitreocola gen. et sp. nov. (Stylonematophyceae), a new red alga on drift glass debris in Oregon and Washington, USA - Gayle I. Hansen; John A. West; Hwan Su Yoon; Christopher D. Goodman; Susan Loiseaux-de Goër; Giuseppe C. Zuccarello (Algae, 2019)

Genetic modifiers of radon-induced lung cancer risk: a genome-wide interaction study in former uranium miners - Albert Rosenberger; Rayjean J. Hung; David C. Christiani; Neil E. Caporaso; Geoffrey Liu; Stig E. Bojesen; Loic Le Marchand; Ch. A. Haiman; Demetrios Albanes; Melinda C. Aldrich; Adonina Tardon; G. Fernández-Tardón; et al. (International Archives of Occupational and Environmental Health, 2018)

Predicted risks of groundwater decline in seasonal wetland plant communities depend on basin morphology - David C. Deane; Claire Harding; Kane T. Aldridge; Abigail M. Goodman; Susan L. Gehrig; Jason M. Nicol; Justin D. Brookes (Wetlands Ecology and Management, 2018)

Riverscape genetics identifies speckled dace (Rhinichthys osculus) cryptic diversity in the Klamath–Trinity Basin - Jesse C. Wiesenfeld; Damon H. Goodman; Andrew P. Kinziger (Conservation Genetics, 2018)

Denaturant-specific effects on the structural energetics of a protein-denatured ensemble - Mahdi Muhammad Moosa; Asha Z. Goodman; Josephine C. Ferreon; Chul Won Lee; Allan Chris M. Ferreon; Ashok A. Deniz (European Biophysics Journal, 2018)

Using environmental report cards to monitor implementation of iwi plans and strategies, including restoration plans - G. T. Tipa; E. K. Williams; C. Van Schravendijk‐Goodman; K. Nelson; W. R. K. Dalton; M. Home; B. Williamson; J. Quinn (New Zealand Journal of Marine and Freshwater Research, 2017)
Protecting valued attributes of a river’s socio‐ecological system demands a more holistic approach to freshwater management. Effective communication is critical to convey the breadth of values and the state of water systems to decision‐makers if they are to make meaningful decisions. Worldwide, environmental report cards are being used to define and measure progress towards environmental sustainability and promoted as an effective communication and engagement tool to galvanise commitment and action. This paper discusses the value of environmental report cards and contends that they can be a valuable integrative tool to support restoration strategies, as well as a way of conveying monitoring results to increase understanding about the health and well‐being of catchments. We present two case studies from the Waikato and Waitaki River in New Zealand where report cards based on eco‐cultural frameworks have been developed that explicitly link indicators that assess the state or condition of the catchment with the vision and goals articulated by iwi/hapū.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Community assembly on isolated islands: macroecology meets evolution - A. J. Rominger; K. R. Goodman; J. Y. Lim; E. E. Armstrong; L. E. Becking; G. M Bennett; M. S. Brewer; D. D. Cotoras; C. P. Ewing; J. Harte; N. D. Martinez; P. M. O'Grady; et al. (Global Ecology and Biogeography, 2016)
Aim Understanding how ecological and evolutionary processes together determine patterns of biodiversity remains a central aim in biology. Guided by ecological theory, we use data from multiple arthropod lineages across the Hawaiian archipelago to explore the interplay between ecological (population dynamics, dispersal, trophic interactions) and evolutionary (genetic structuring, adaptation, speciation, extinction) processes. Our goal is to show how communities develop from the dynamic feedbacks that operate at different temporal and spatial scales. Location The Hawaiian islands (19–22° N , 155–160° W ). Methods We synthesize genetic data from selected arthropods across the Hawaiian archipelago to determine the relative role of dispersal and in situ differentiation across the island chronosequence. From four sites on three high islands with geological ages ranging from Results From the perspective of the island chronosequence we show that species at lower trophic levels develop population genetic structure at smaller temporal and spatial scales than species at higher trophic levels. Network nestedness decreases while modularity increases with habitat age. Single‐island endemics exhibit more specialization than broadly distributed species, but both show the least specialization in communities on middle‐aged substrates. Plant–herbivore networks also show the least deviation from theoretical predictions in middle‐aged communities. Main conclusions The application of ecological theory to island chronosequences can illuminate feedbacks between ecological and evolutionary processes in community assembly. We show how patterns of population genetic structure, decreasing network nestedness, increasing network modularity and increased specialization shift from early assembly driven by immigration, to in situ diversification after > 1 Myr. Herbivore–plant communities only transiently achieve statistical steady state during assembly, presumably due to incomplete assembly from dispersal in the early stages, and the increasing influence of island ontogeny on older islands.

Non-cultured faecal and gastrointestinal seed samples fail to detect Trichomonad infection in clinically and sub-clinically infected columbid birds - Jenny C. Dunn; Jennifer E. Stockdale; Alexandra McCubbin; Rebecca C. Thomas; Simon J. Goodman; Philip V. Grice; Antony J. Morris; Keith C. Hamer; William O. C. Symondson (Conservation Genetics Resources, 2016)

The influence of climate on avian nest construction across large geographical gradients - C. B. Heenan; B. A. Goodman; C. R. White (Global Ecology and Biogeography, 2015)
Aim Nest microclimate is a critical determinant of the survival and development of embryonic and juvenile birds. While abiotic variables such as temperature, precipitation and elevation will influence the conditions experienced by offspring within the nest, parent birds may also exercise some control through nest design and the selection of construction material. The aim of this study is to determine whether avian nest construction and the composition of nest construction material is influenced by geographical variation in climate. In addition, this study aims to address whether the correlation between nest construction and elevation highlighted by other studies is independent of the association between elevation and climate, or if other unmeasured variables are at play. Location A ustralia Methods We measured the structural and thermal properties of 201 cup‐shaped nests, from 36 A ustralian passerine species, and related these to temperature, precipitation and elevation. Results The rate of heat loss from avian nests is correlated with temperature, precipitation and elevation. Birds that construct nests in cool climates use well‐insulating materials irrespective of precipitation, while birds in warm climates use poorly insulating materials when exposed to high rainfall but not when exposed to low rainfall. Main conclusions Local climate influences the construction of nests, through modification of the materials used, and therefore the rate of heat loss from the nest as a whole. In many climates, birds use well‐insulating materials; however, birds breeding in warm and wet climates construct their nests with materials that have a higher thermal conductivity. Such nests are possibly less absorptive and able to dry out faster following a rain event, to restore the insulating function of the nest. These findings highlight the importance of studies over large geographical scales for understanding nest construction by birds.

CMV in the gut: a critical review of CMV detection in the immunocompetent host with colitis - A. L. Goodman; C. D. Murray; J. Watkins; P. D. Griffiths; D. P. Webster (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

αvβ3, αvβ5 and αvβ6 integrins in brain metastases of lung cancer - Anna Sophie Berghoff; Astrid Kerstin Kovanda; Thomas Melchardt; Rupert Bartsch; Johannes A. Hainfellner; Bence Sipos; Jens Schittenhelm; Christoph C. Zielinski; Georg Widhalm; Karin Dieckmann; Michael Weller; Simon L. Goodman; et al. (Clinical & Experimental Metastasis, 2014)

Improved allometric models to estimate the aboveground biomass of tropical trees - Jérôme Chave; Maxime Réjou‐Méchain; Alberto Búrquez; Emmanuel Chidumayo; Matthew S. Colgan; Welington B.C. Delitti; Alvaro Duque; Tron Eid; Philip M. Fearnside; Rosa C. Goodman; Matieu Henry; Angelina Martínez‐Yrízar; et al. (Global Change Biology, 2014)
Terrestrial carbon stock mapping is important for the successful implementation of climate change mitigation policies. Its accuracy depends on the availability of reliable allometric models to infer oven‐dry aboveground biomass of trees from census data. The degree of uncertainty associated with previously published pantropical aboveground biomass allometries is large. We analyzed a global database of directly harvested trees at 58 sites, spanning a wide range of climatic conditions and vegetation types (4004 trees ≥ 5 cm trunk diameter). When trunk diameter, total tree height, and wood specific gravity were included in the aboveground biomass model as covariates, a single model was found to hold across tropical vegetation types, with no detectable effect of region or environmental factors. The mean percent bias and variance of this model was only slightly higher than that of locally fitted models. Wood specific gravity was an important predictor of aboveground biomass, especially when including a much broader range of vegetation types than previous studies. The generic tree diameter–height relationship depended linearly on a bioclimatic stress variable E , which compounds indices of temperature variability, precipitation variability, and drought intensity. For cases in which total tree height is unavailable for aboveground biomass estimation, a pantropical model incorporating wood density, trunk diameter, and the variable E outperformed previously published models without height. However, to minimize bias, the development of locally derived diameter–height relationships is advised whenever possible. Both new allometric models should contribute to improve the accuracy of biomass assessment protocols in tropical vegetation types, and to advancing our understanding of architectural and evolutionary constraints on woody plant development.

Invasion genetics of a human commensal rodent: the black rat R attus rattus in M adagascar - C. Brouat; C. Tollenaere; A. Estoup; A. Loiseau; S. Sommer; R. Soanandrasana; L. Rahalison; M. Rajerison; S. Piry; S. M. Goodman; J.‐M. Duplantier (Molecular Ecology, 2014)
Studies focusing on geographical genetic patterns of commensal species and on human history complement each other and provide proxies to trace common colonization events. On Madagascar, the unintentional introduction and spread of the commensal species R attus rattus by people may have left a living clue of human colonization patterns and history. In this study, we addressed this question by characterizing the genetic structure of natural populations of R . rattus using both microsatellites and mitochondrial sequences, on an extensive sampling across the island. Such data sets were analysed by a combination of methods using population genetics, phylogeography and approximate B ayesian computation. Our results indicated two introduction events to M adagascar from the same ancestral source of R . rattus , one in the extreme north of the island and the other further south. The latter was the source of a large spatial expansion, which may have initially started from an original point located on the southern coast. The inferred timing of introduction events—several centuries ago—is temporally congruent with the A rabian trade network in the I ndian O cean, which was flourishing from the middle of the first millennium.

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Nitrogen fertilization of black walnut (Juglans nigra L.) during plantation establishment. Physiology of production - Rosa C. Goodman; Juan A. Oliet; Joshua L. Sloan; Douglass F. Jacobs (European Journal of Forest Research, 2014)

An institutional strategy to increase minority recruitment to therapeutic trials - Victoria V. Anwuri; Lannis E. Hall; Katherine Mathews; Brian C. Springer; Jennifer R. Tappenden; Dione M. Farria; Sherrill Jackson; Melody S. Goodman; Timothy J. Eberlein; Graham A. Colditz (Cancer Causes & Control, 2013)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Stable isotope ratios of a tropical marine predator: confounding effects of nutritional status during growth - Larisa Lee Cruz; Rona A. R. McGill; Simon J. Goodman; Keith C. Hamer (Marine Biology, 2012)

Chromosome 15q24-25.1 variants, diet, and lung cancer susceptibility in cigarette smokers - Lori C. Sakoda; Melissa M. Loomis; Jennifer A. Doherty; Marian L. Neuhouser; Matt J. Barnett; Mark D. Thornquist; Noel S. Weiss; Gary E. Goodman; Chu Chen (Cancer Causes & Control, 2011)

Monte Carlo Simulation and Well Testing Applied in Evaluating Reservoir Properties in a Deforming Longwall Overburden - C. Özgen Karacan; Gerrit V. R. Goodman (Transport in Porous Media, 2011)

Health risk assessment of ochratoxin A for all age-sex strata in a market economy - T. Kuiper-Goodman; C. Hilts; S.M. Billiard; Y. Kiparissis; I.D.K. Richard; S. Hayward (Food Additives & Contaminants: Part A, 2010)

Role of dopamine transporters in the behavioral effects of 3,4-methylenedioxymethamphetamine (MDMA) in nonhuman primates - William E. Fantegrossi; Rayna M. Bauzo; Daniel M. Manvich; Jose C. Morales; John R. Votaw; Mark M. Goodman; Leonard L. Howell (Psychopharmacology, 2009)

Phylogeography of the magpie‐robin species complex (Aves: Turdidae: Copsychus ) reveals a Philippine species, an interesting isolating barrier and unusual dispersal patterns in the Indian Ocean and Southeast Asia - Frederick H. Sheldon; David J. Lohman; Haw C. Lim; Fasheng Zou; Steven M. Goodman; Dewi M. Prawiradilaga; Kevin Winker; Thomas M. Braile; Robert G. Moyle (Journal of Biogeography, 2009)
Aim The oriental magpie‐robin ( Copsychus saularis ) of South and Southeast Asia is a phenotypically variable species that appears to be closely related to two endemic species of the western Indian Ocean: the Madagascar magpie‐robin ( Copsychus albospecularis ) and the Seychelles magpie‐robin ( Copsychus sechellarum ). This unusual distribution led us to examine evolutionary relationships in magpie‐robins, and also the taxonomic significance of their plumage variation, via a molecular phylogenetic and population genetic analysis of C. saularis and C. albospecularis . Location Southern Asia from Nepal across Indochina to southern China, and the Indian Ocean from Madagascar to the Greater Sunda and Philippine islands. Methods We sequenced 1695 nucleotides of mitochondrial DNA comprising the complete second subunit of the nicotinamide adenine dinucleotide dehydrogenase (ND2) gene and 654 bases of the cytochrome c oxidase subunit I (COI) region in 51 individuals of eight C. saularis subspecies, 10 individuals of C. albospecularis (one subspecies) and single individuals of two other Copsychus species as outgroups. The data were analysed phylogenetically, with maximum likelihood, Bayesian, relaxed clock and parsimony methods, and geographically for patterns of genetic diversity. Results Phylogenetic analysis indicated that C. albospecularis lies within the nominal C. saularis , making C. saularis polyphyletic. Malagasy and non‐Philippine Asian populations form a monophyletic group that is sister to a clade of Philippine populations. Within non‐Philippine Asian populations, two groups are evident: black‐bellied birds in the eastern Greater Sunda islands and white‐bellied birds in the western Sundas and on mainland Asia. Main conclusions The phylogeny of magpie‐robins suggests a novel pattern of dispersal and differentiation in the Old World. Ancestral magpie‐robins appear to have spread widely among islands of the Indian Ocean in the Pliocene, probably aided by their affinity for coastal habitats. Populations subsequently became isolated in island groups, notably the Philippines, Madagascar and the Greater Sundas, leading to speciation in all three areas. Isolation in the Philippines may have been aided by competitive exclusion of C. saularis from Palawan by a congener, the white‐vented shama ( Copsychus niger ). In the Greater Sundas, white‐bellied populations appear to have invaded Borneo and Java recently, where they hybridize with resident black‐bellied birds.

Impact of socioeconomic status on cancer incidence and stage at diagnosis: selected findings from the surveillance, epidemiology, and end results: National Longitudinal Mortality Study - Limin X. Clegg; Marsha E. Reichman; Barry A. Miller; Benjamin F. Hankey; Gopal K. Singh; Yi Dan Lin; Marc T. Goodman; Charles F. Lynch; Stephen M. Schwartz; Vivien W. Chen; Leslie Bernstein; Scarlett L. Gomez; et al. (Cancer Causes & Control, 2009)

Development of a Methodology for Successful Multigeneration Life-Cycle Testing of the Estuarine Sheepshead Minnow, Cyprinodon variegatus - G. M. Cripe; B. L. Hemmer; L. R. Goodman; J. C. Vennari (Archives of Environmental Contamination and Toxicology, 2009)

Use of selection with recurrent backcrossing and QTL mapping to identify loci contributing to southern leaf blight resistance in a highly resistant maize line - John C. Zwonitzer; David M. Bubeck; Dinakar Bhattramakki; Major M. Goodman; Consuelo Arellano; Peter J. Balint-Kurti (Theoretical and Applied Genetics, 2009)

Early detection of oxidized surfaces using Shewanella oneidensis MR-1 as a tool - M. S. Waters; E. C. Salas; S. D. Goodman; F. E. Udwadia; K. H. Nealson (Biofouling, 2009)

E–C coupling and contractile characteristics of mechanically skinned single fibres from young rats during rapid growth and maturation - C. A. Goodman; R. Blazev; J. Kemp; G. M. M. Stephenson (Pflügers Archiv - European Journal of Physiology, 2008)

Simulation of networks of spiking neurons: A review of tools and strategies - Romain Brette; Michelle Rudolph; Ted Carnevale; Michael Hines; David Beeman; James M. Bower; Markus Diesmann; Abigail Morrison; Philip H. Goodman; Frederick C. Harris; Milind Zirpe; Thomas Natschläger; et al. (Journal of Computational Neuroscience, 2007)

Chromosomal evolution in tenrecs (Microgale and Oryzorictes, Tenrecidae) from the Central Highlands of Madagascar - C. Gilbert; S. M. Goodman; V. Soarimalala; L. E. Olson; P. C. M. O’Brien; F. F. B. Elder; F. Yang; M. A. Ferguson-Smith; T. J. Robinson (Chromosome Research, 2007)

3-Hydroxyglutaric acid is transported via the sodium-dependent dicarboxylate transporter NaDC3 - Franziska Stellmer; Britta Keyser; Birgitta C. Burckhardt; Hermann Koepsell; Thomas Streichert; Markus Glatzel; Sabrina Jabs; Joachim Thiem; Wilhelm Herdering; David M. Koeller; Stephen I. Goodman; Zoltan Lukacs; et al. (Journal of Molecular Medicine, 2007)

Proof of concept percutaneous treatment system to enable fast and finely controlled ablation of biological tissue - C. P. Hancock; S. Chaudhry; P. Wall; A. M. Goodman (Medical & Biological Engineering & Computing, 2007)

Quality of race, Hispanic ethnicity, and immigrant status in population-based cancer registry data: implications for health disparity studies - Limin X. Clegg; Marsha E. Reichman; Benjamin F. Hankey; Barry A. Miller; Yi D. Lin; Norman J. Johnson; Stephen M. Schwartz; Leslie Bernstein; Vivien W. Chen; Marc T. Goodman; Scarlett L. Gomez; John J. Graff; et al. (Cancer Causes & Control, 2007)

Linking soil process and microbial ecology in freshwater wetland ecosystems - Jessica L. M. Gutknecht; Robert M. Goodman; Teri C. Balser (Plant and Soil, 2006)

Interspersed normoxia during live high, train low interventions reverses an early reduction in muscle Na+, K+ATPase activity in well-trained athletes - R. J. Aughey; S. A. Clark; C. J. Gore; N. E. Townsend; A. G. Hahn; T. A. Kinsman; C. Goodman; C. M. Chow; D. T. Martin; J. A. Hawley; M. J. McKenna (European Journal of Applied Physiology, 2006)

Microbial response over time to hydrologic and fertilization treatments in a simulated wet prairie - Jessica L Mentzer; Robert M Goodman; Teri C Balser (Plant and Soil, 2006)

Ecological Thresholds: The Key to Successful Environmental Management or an Important Concept with No Practical Application? - Peter M. Groffman; Jill S. Baron; Tamara Blett; Arthur J. Gold; Iris Goodman; Lance H. Gunderson; Barbara M. Levinson; Margaret A. Palmer; Hans W. Paerl; Garry D. Peterson; N. LeRoy Poff; David W. Rejeski; et al. (Ecosystems, 2006)

COLONIZATION HISTORY OF THE BALTIC HARBOR SEALS: INTEGRATING ARCHAEOLOGICAL, BEHAVIORAL, AND GENETIC DATA - Tero Harkonen; Karin C. Harding; Simon J. Goodman; Kerstin Johannesson (Marine Mammal Science, 2005)

Book Review:E.J. Anaisse, M.R. McGinnis, M.A. Pfaller, eds. Clinical Mycology, 2003, Churchill Livingstone, London, UK; 2003, 608 pp., $139.00. - Alice C. Thornton; Norman L. Goodman (Mycopathologia, 2005)

Sediment Toxicity and Community Composition of Benthos and Colonized Periphyton in the Everglades–Florida Bay Transitional Zone - Michael A. Lewis; Larry R. Goodman; John M. Macauley; James C. Moore (Ecotoxicology, 2004)

Identification of chemically modified peptide from poly(D,L-lactide-co-glycolide) microspheres under in vitro release conditions - Santos B. Murty; Jack Goodman; B. C. Thanoo; Patrick P. DeLuca (AAPS PharmSciTech, 2003)

The Effects of Urbanization on the Chemical Quality of Three Tidal Bayous in the Gulf of Mexico - Michael A. Lewis; James C. Moore; Larry R. Goodman; James M. Patrick; Roman S. Stanley; Thomas H. Roush; Robert L. Quarles (Water, Air, & Soil Pollution, 2001)

Assessing Landscape Condition Relative to Water Resources in the Western United States: A Strategic Approach - K. Bruce Jones; Daniel T. Heggem; Timothy G. Wade; Anne C. Neale; Donald W. Ebert; Maliha S. Nash; Megan H. Mehaffey; Karl A. Hermann; Anthony R. Selle; Scott Augustine; Iris A. Goodman; Joel Pedersen; et al. (Environmental Monitoring and Assessment, 2000)

Nanoscale topography of the basement membrane underlying the corneal epithelium of the rhesus macaque - G. A. Abrams; S. L. Goodman; P. F. Nealey; M. Franco; C. J. Murphy (Cell and Tissue Research, 2000)

IN VITRO HOST RANGE STUDIES WITH A NEW BACULOVIRUS ISOLATE FROM THE DIAMONDBACK MOTH PLUTELLA XYLOSTELLA (L.) (PLUTELLIDAE: LEPIDOPTERA) - C. W. KARIUKI; A. H. MCINTOSH; C. L. GOODMAN (In Vitro Cellular & Developmental Biology - Animal, 2000)

Update on the Phylogenetic Systematics of New World Monkeys: Further DNA Evidence for Placing the Pygmy Marmoset (Cebuella) within the Genus Callithrix - C. M. L. Barroso; H. Schneider; M. P. C. Schneider; I. Sampaio; M. L. Harada; J. Czelusniak; M. Goodman (International Journal of Primatology, 1997)

Phylogeny and Evolution of Selected Primates as Determined by Sequences of the ε-Globin Locus and 5′ Flanking Regions - Calvin A. Porter; Scott L. Page; John Czelusniak; Horacio Schneider; Maria Paula C. Schneider; Iracilda Sampaio; Morris Goodman (International Journal of Primatology, 1997)

Modulation of N-myc expression alters the invasiveness of neuroblastoma - Lisa A. Goodman; Brian C. S. Liu; Carol J. Thiele; Mary Lou Schmidt; Susan L. Cohn; Joyce M. Yamashiro; David S. M. Pai; Naohiko Ikegaki; Randal K. Wada (Clinical & Experimental Metastasis, 1997)

New isozyme systems for maize (Zea mays L.): Aconitate hydratase, adenylate kinase, NADH dehydrogenase, and shikimate dehydrogenase - Jonathan F. Wendel; Major M. Goodman; C. W. Stuber; J. B. Beckett (Biochemical Genetics, 1988)

New isozyme systems for maize (Zea mays L.): Aconitate hydratase, adenylate kinase, NADH dehydrogenase, and shikimate dehydrogenase - Jonathan F. Wendel; Major M. Goodman; C. W. Stuber; J. B. Beckett (Biochemical Genetics, 1988)

Description of a genetic polymorphism of a human proline-rich salivary protein, Pc, and its relationship to other proteins in the salivary protein complex (SPC) - Robert C. Karn; Patricia A. Goodman; Pao-Lo Yu (Biochemical Genetics, 1985)

Inheritance, intracellular localization, and genetic variation of phosphoglucomutase isozymes in maize (Zea mays L.) - C. W. Stuber; M. M. Goodman (Biochemical Genetics, 1983)

Human partoid size polymorphism (Ps): Characterization of two allelic products, Ps 1 and 2, by limited proteolysis - Patricia A. Goodman; Robert C. Karn (Biochemical Genetics, 1983)

Genetic control and racial variation of ?-glucosidase isozymes in maize (Zea mays L.) - C. W. Stuber; M. M. Goodman; F. M. Johnson (Biochemical Genetics, 1977)